Compound crystal form as well as preparation method and application thereof

By preparing nucleosides with specific crystal forms, the problem of purity control of phosphoramidite monomers and the problem that protective nucleosides easily absorb water in the existing technology is solved, and higher purity and yield are achieved.

CN119350413APending Publication Date: 2025-01-24TIANJIN QUANHECHENG TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411309847.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The prior art is difficult to effectively control the purity of the phosphoramidite monomer, and the amorphous solid powder of protective nucleosides is easy to absorb water, affecting the purity and yield of the product.

Method used

Provide a compound with a specific crystal type, its X-ray powder diffraction diagram feature peak 2 θ includes 10.00 ° ± 0.2 °, 12.08 ° ± 0.2 °, 14.76 ° ± 0.2 °, etc. And cool down the crystal and prepare a stable crystal type.

Benefits of technology

The method prepared by this method is not easy to deteriorate, low water content and diversification, and high melting point, which significantly improves the purity and yield of phosphoricide monomers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350413A_ABST
    Figure CN119350413A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of medicine, and discloses a compound crystal form and a preparation method and application thereof, the compound has a structure shown in a formula (1), and the characteristic peaks 2 theta of an X-ray powder diffraction pattern of the crystal form comprise 10.00 + / -0.2 degrees, 12.08 + / -0.2 degrees, 14.76 + / -0.2 degrees, 16.90 + / -0.2 degrees, 18.90 + / -0.2 degrees, 19.30 + / -0.2 degrees, 20.16 + / -0.2 degrees, 21.38 + / -0.2 degrees, 23.96 + / -0.2 degrees and 24.36 + / -0.2 degrees; the purity change of the nucleoside with the specific crystal form is small along with the prolonging of the placement time, which indicates that the crystal form prepared by the method is not easy to deteriorate and is easy to store. The nucleoside with the specific crystal form has a higher melting point and lower water content and hygroscopicity. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of medical technology, and in particular to a compound crystal form and a preparation method and application thereof. Background Art

[0002] Nucleic acid drugs, as the third largest type of drugs after small molecule drugs and antibody drugs, have become a global focus and hotspot for biopharmaceutical companies. Currently, there are 14 small nucleic acid drugs approved for marketing worldwide. As a key material for the synthesis of nucleic acid drugs, the purity control of phosphoramidite monomers is very important. The supply of nucleoside monomers that meet the quality requirements is a key factor in the commercialization of nucleic acid drugs. The purity requirement of phosphoramidite monomers is generally ≥99.0%, and the difficulty of quality control is even higher than that of general small molecule APIs (Active pharmaceutical ingredients). It takes a long time for companies to accumulate technology to meet the quality control requirements of phosphoramidite monomers. The synthesis route of phosphoramidite monomers usually includes: (1) treating the nucleoside with acyl chloride or anhydride to add a protecting group to the base; (2) then using DMTrCl reagent to add a DMTr protecting group to the 5' to become a protected nucleoside; (3) then using a phosphorus reagent to phosphitylate the phosphoramidite monomer. Among them, the quality of the protective nucleoside directly affects the purity of the phosphoramidite monomer. Moreover, the phosphitylation reaction needs to be carried out in a water-free environment. Water will directly affect the purity and yield of the phosphoramidite monomer product. The existing protective nucleosides are mostly amorphous solid powders, which are very easy to absorb water during storage. Therefore, studying a protective nucleoside that can be stably preserved is of great significance for improving the purity and yield of the phosphoramidite monomer product. Summary of the invention

[0003] The purpose of the present invention is to overcome the above-mentioned technical problems existing in the prior art and to provide a compound crystal form and a preparation method and application thereof.

[0004] In order to achieve the above-mentioned object, the first aspect of the present invention provides a crystalline form of a compound represented by formula (1), wherein the characteristic peaks 2θ of the X-ray powder diffraction pattern of the crystalline form include 10.00°±0.2°, 12.08°±0.2°, 14.76°±0.2°, 16.90°±0.2°, 18.90°±0.2°, 19.30°±0.2°, 20.16°±0.2°, 21.38°±0.2°, 23.96°±0.2°, 24.36°±0.2°;

[0005]

[0006] The second aspect of the present invention provides a method for preparing the above-mentioned crystal form, which comprises: mixing the compound represented by formula (1) with acetonitrile, heating to dissolve the compound represented by formula (1), and then cooling and crystallizing to obtain the crystal form of the compound represented by formula (1).

[0007] The third aspect of the present invention provides the use of the crystalline form of the compound represented by formula (1) described above in improving the purity of phosphoramidite monomers; preferably, the use includes using the compound represented by formula (1) having the crystalline form described above as a raw material for synthesizing phosphoramidite monomers.

[0008] Through the above technical solution, the present invention achieves the following beneficial effects:

[0009] The purity of the nucleoside with a specific crystal form of the present invention changes slightly with the extension of the storage time, which indicates that the crystal form prepared by the method of the present invention is not easy to deteriorate and is easy to preserve.

[0010] The nucleoside with a specific crystal form of the present invention has a higher melting point and lower water content and hygroscopicity. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 It is the XRD pattern of the product prepared in Example. DETAILED DESCRIPTION

[0012] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0013] In a first aspect, the present invention provides a crystalline form of a compound represented by formula (1), wherein the characteristic peaks 2θ of the X-ray powder diffraction pattern of the crystalline form include 10.00°±0.2°, 12.08°±0.2°, 14.76°±0.2°, 16.90°±0.2°, 18.90°±0.2°, 19.30°±0.2°, 20.16°±0.2°, 21.38°±0.2°, 23.96°±0.2°, and 24.36°±0.2°;

[0014]

[0015] According to the present invention, preferably, the characteristic peak 2θ of the X-ray powder diffraction pattern of the crystal form also includes 8.98°±0.2°, 13.6°±0.2°, 17.8°±0.2°, 22.80°±0.2°, 25.22°±0.2°, 27.30°±0.2°, 28.20°±0.2°, 29.26°±0.2°, 30.10°±0.2°, 30.72°±0.2°, 31.30°±0.2°, 32.40°±0.2°, 34.26°±0.2°, 35.92°±0.2°, 36.90°±0.2°, and 38.76°±0.2°.

[0016] According to the present invention, preferably, the structure of the compound represented by formula (1) is

[0017]

[0018] According to the present invention, preferably, the X-ray powder diffraction pattern of the crystal form is as follows Figure 1 shown.

[0019] According to the present invention, preferably, the melting point of the crystalline form is 137-148°C.

[0020] According to the present invention, preferably, the water content in the crystalline form is less than 0.5 wt %. More preferably, the water content in the crystalline form is less than 0.3 wt %.

[0021] According to the present invention, preferably, the hygroscopicity of the crystal form is lower than 102 wt %. More preferably, the hygroscopicity of the crystal form is lower than 101.6 wt %.

[0022] According to the present invention, preferably, the content of acetonitrile in the crystalline form is less than 3% by weight.

[0023] According to the present invention, preferably, the interplanar spacing of the crystal form is 0.2-1 nm, and the half-peak width is 0.1-1 nm. More preferably, the interplanar spacing of the characteristic peak of the crystal form at 2θ≤25° is 0.36-1 nm. Further preferably, the interplanar spacing and half-peak width of the crystal form at different characteristic peaks are shown in Table 1-A. Table 1-A

[0024]

[0025] In the present invention,

[0026] The second aspect of the present invention provides a method for preparing the above-mentioned crystal form, which comprises: mixing the compound represented by formula (1) with acetonitrile, heating to dissolve the compound represented by formula (1), and then cooling and crystallizing to obtain the crystal form of the compound represented by formula (1).

[0027] According to the present invention, preferably, the amount of acetonitrile used is 6-12 mL (for example, 6 mL, 6.5 mL, 7 mL, 7.5 mL, 8 mL, 8.5 mL, 9 mL, 9.5 mL, 10 mL, 10.5 mL, 11 mL, 12 mL, and ranges consisting of any two of the above) per gram of the compound represented by formula (1).

[0028] According to the present invention, preferably, the heating temperature is 65-85°C (for example, it can be 65°C, 70°C, 75°C, 80°C, 85°C, and a range consisting of any two of the above points).

[0029] According to the present invention, preferably, the crystallization temperature is 5-25° C., preferably, the crystallization is performed under stirring, and the crystallization time can be 8-12 hours.

[0030] According to the present invention, preferably, the method for preparing the compound represented by formula (1) comprises: mixing the compound represented by formula (II) with dimethoxytriphenylmethane in the presence of a base and a solvent, and then reacting to obtain the compound represented by formula (1);

[0031]

[0032] According to the present invention, preferably, the compound represented by formula (II) is

[0033]

[0034] According to the present invention, preferably, the solvent is at least one of pyridine, dichloromethane and dimethylformamide.

[0035] According to the present invention, preferably, the base comprises at least one of pyridine, triethylamine and N,N-diisopropylethylamine.

[0036] According to the present invention, preferably, with respect to each millimole of the compound represented by formula (II), the amount of triethylamine used is 1-20 mmol, the amount of solvent used is 3-8 mL, and the amount of dimethoxytriphenylmethane used is 1-2 mmol.

[0037] According to the present invention, preferably, the compound represented by formula (II) is mixed with dimethoxytriphenylmethane by dropwise adding a dichloromethane solution containing dimethoxytriphenylmethane to the compound represented by formula (II). More preferably, the dropwise addition rate is 10-50 mL / h, and the concentration of dimethoxytriphenylmethane in the dichloromethane solution containing dimethoxytriphenylmethane is 0.5-0.8 mol / L.

[0038] According to the present invention, preferably, the reaction conditions include: temperature of 15-20° C., and time of 10-16 h.

[0039] According to the present invention, preferably, the method for preparing the compound of formula (1) further comprises: after the reaction is completed, adding a quencher to the reaction system for quenching, then extracting with dichloromethane to obtain an organic phase containing the compound of formula (II), then washing the organic phase with saturated lemon water solution, saturated sodium chloride, and saturated sodium bicarbonate, respectively, and then drying to obtain a crude product of the compound of formula (1). The purity of the compound of formula (1) (crude product) prepared by this method is 70-90%.

[0040] The third aspect of the present invention provides the use of the crystalline form of the compound represented by formula (1) described above in improving the purity of phosphoramidite monomers; preferably, the use includes using the compound represented by formula (1) having the crystalline form described above as a raw material for synthesizing phosphoramidite monomers.

[0041] The synthetic route for preparing phosphoramidite monomers using nucleosides is as follows:

[0042]

[0043] According to the present invention, preferably, the synthesis route of the phosphoramidite monomer using the compound represented by formula (1) in the above-mentioned crystalline form is as follows:

[0044]

[0045] The present invention will be described in detail below by way of examples. In the following examples,

[0046] X-ray diffractometer conditions: the model of the instrument is Ultima IV, the manufacturer is Japan Rigaku Corporation, the voltage is 40 kV, the current is 40 mA, the scanning range (2θ): 3-90°, the step size: 0.02°.

[0047] Preparation Example 1

[0048] This preparation example is used to illustrate the method of synthesizing the compound represented by formula (1) using the compound represented by formula (II). The synthesis route is as follows:

[0049]

[0050] Wherein, DMTr is dimethoxytrityl.

[0051] The compound represented by formula (II) is added to the solvent pyridine, and then triethylamine is added, and then the reaction system is cooled to 0-5°C, and a dichloromethane solution containing dimethoxytriphenylmethane (DMTrCl) with a concentration of 0.7 mol / L is added dropwise to the reaction system at a rate of 30 mL / h. After the addition is completed, the reaction system is heated to room temperature (about 15-20°C) and reacted for 12 hours. HPLC detection shows that the remaining raw material is less than 5%, and the reaction is stopped. At 0-5°C, water (the volume of water is 5 times the volume of the reaction system) is slowly added to the reaction system for quenching, and then Dichloromethane (the volume of dichloromethane is 10 times the volume of the reaction system) is added to extract and separate the liquid, and then the organic phase is washed 6 times with a saturated citric acid aqueous solution (the single volume of the saturated citric acid aqueous solution is 5 times the volume of the organic phase) until the TLC plate shows that there is basically no pyridine remaining in the organic phase, and then saturated sodium chloride aqueous solution, saturated sodium bicarbonate aqueous solution, saturated sodium chloride aqueous solution, and each washing are used in sequence, and then dried (drying temperature is 15-25°C, drying time is 0.1-1h) and concentrated to obtain a crude product containing the compound represented by formula (1). Wherein, the amount of triethylamine used is 3.75mmol, the amount of solvent pyridine used is 4mL, and the amount of dimethoxytriphenylmethane used is 2mmol per millimole of the compound represented by formula (II).

[0052] HPLC analysis showed that the purity of the crude product containing the compound represented by formula (1) was 77%.

[0053] A crude product containing the compound represented by formula (1) 1 H NMR(400MHz,DMSO-d6)δ11.19(s,1H),8.66(s,1H),8.58(s,1H),8.16–7.93(m,2H),7.73–7.6 0(m,1H),7.55(t,J=7.6Hz,2H),7.39–7.27(m,2H),7.27–7.09(m,7H),6.89–6.70(m,4H),6.50 (t,J=6.4Hz,1H),5.42(d,J=4.4Hz,1H),4.52(p,J=4.8Hz,1H),4.03(q,J=4.8Hz,1H),3.71(d ,J=3.2Hz,6H),2.95(dt,J=13.2,6.4Hz,1H),2.40(ddd,J=13.2,6.8,4.6Hz,1H),2.08(s,1H).

[0054] Example 1

[0055] The crude product containing the compound of formula (1) obtained in Preparation Example 1 was added to acetonitrile (8 mL of acetonitrile was used per gram of the compound of formula (1)), and then the temperature was raised to 70°C to completely dissolve the crude product; then the temperature was lowered to 20°C at a cooling rate of 0.1°C / min, and then crystallized for 12 hours under stirring; then filtered and dried (drying temperature was 50°C, and drying time was 9 hours) to obtain a white crystalline product. The yield of the product was 90%. The obtained solid product was subjected to X-ray diffraction powder diffraction determination using Cu-ka rays, and the obtained XRD spectrum was as shown below: Figure 1 As shown, the XRD spectrum data is shown in Table 1-B.

[0056] Table 1-B

[0057]

[0058] Example 2

[0059] The crude product containing the compound of formula (1) obtained in Preparation Example 1 was added to acetonitrile (the amount of acetonitrile was 10 mL per gram of the compound of formula (1)), and then the temperature was raised to 80°C to completely dissolve the crude product; then the temperature was lowered to 20°C at a cooling rate of 0.2°C / min, and then crystallized for 10 hours under stirring; then filtered and dried (drying temperature was 50°C, and drying time was 9 hours) to obtain a white crystalline product. The yield of the product was 92%. The obtained solid product was subjected to X-ray diffraction powder diffraction determination using Cu-ka rays, and the data of the XRD spectrum were basically consistent with those in Example 1, and are not shown here.

[0060] Comparative Example 1

[0061] The crude product containing the compound of formula (1) prepared in Preparation Example 1 is added with dichloromethane to dissolve to obtain a dichloromethane solution containing the compound of formula (1), and then the dichloromethane solution containing the compound of formula (1) is quickly added dropwise to n-heptane. After the addition is completed, it is filtered and (the drying temperature is 50° C. and the drying time is 9 hours) to obtain a solid product, and the yield of the solid product is 90%. Wherein, the amount of dichloromethane is 3 mL and the amount of n-heptane is 10 mL per gram of the compound of formula (1). The obtained solid product is subjected to X-ray diffraction powder diffraction measurement using Cu-ka rays, and there is no obvious characteristic peak in the XRD spectrum, that is, the solid product is an amorphous powder.

[0062] Comparative Example 2

[0063] The method of Comparative Example 1 was followed, except that the dichloromethane was replaced with an equal volume of ethyl acetate. The X-ray diffraction powder diffraction was measured using Cu-ka rays, and there was no obvious characteristic peak in the XRD spectrum, that is, the obtained product was an amorphous (powder) solid. The yield of the product was 85%.

[0064] Comparative Example 3

[0065] The method of comparative example 1 was followed, except that dichloromethane was replaced by an equal volume of N,N-dimethylformamide, and n-heptane was replaced by purified water. Cu-ka rays were used for X-ray diffraction powder diffraction determination, and there was no obvious characteristic peak in the XRD spectrum, that is, the obtained product was an amorphous (powder) solid. The yield of the product was 90%.

[0066] Test Case

[0067] The crystals obtained in the above examples and the powder solids obtained in the comparative examples were tested for melting point, water content (KF), hygroscopicity and stability.

[0068] (1) Melting point test method: The melting point was tested using a fully automatic video melting point apparatus (manufacturer: Haineng Future Instrument Technology Group Co., Ltd., model: MP470). The temperature was raised to 90°C at a heating rate of 1°C / min, and then the sample was placed in the fully automatic video melting point apparatus to test the melting point of the sample. The test results are shown in Table 2.

[0069] (2) Water content test method: The water content was tested by Coulometric Karl Fischer titration using an automatic sampler moisture analyzer (manufacturer: Shanghai Hegong Scientific Instrument Co., Ltd., model AKF-CAS6), wherein the furnace temperature was 150° C. The test results are shown in Table 2.

[0070] (3) Hygroscopicity test method: a certain mass of the sample to be tested is placed in an open bottle, and then the open bottle is placed in a constant temperature dryer, which is filled with a saturated ammonium chloride aqueous solution. After being placed at 25±1°C for 24 hours, the weight of the sample after absorbing the moisture in the constant temperature dryer is weighed. The calculation formula for hygroscopicity is: (weight of the sample after absorbing the moisture in the constant temperature dryer - weight of the sample after absorbing the moisture in the constant temperature dryer) ÷ weight of the sample after absorbing the moisture in the constant temperature dryer × 100%. The test results are shown in Table 2.

[0071] (4-1) The sample to be tested was placed under the conditions of 40±2°C and 75±5%RH (relative humidity) for 0 day (T0), 5 days (5D), 10 days (10D), one month (1M), and three months (3M), and then the purity change of the product was tested by high performance liquid chromatography (HPLC). The test results are shown in Table 3.

[0072] (4-2) The sample to be tested was placed under the conditions of 50±5°C and 75±5%RH (relative humidity) for 0 day (T0), 5 days (5D), 10 days (10D), one month (1M), and three months (3M), and then the purity change of the product was tested by high performance liquid chromatography (HPLC). The test results are shown in Table 3.

[0073] Table 2

[0074] Melting point(℃) Water content (weight %) Hygroscopicity (weight %) Example 1 138.4-147.9 0.29681 101.53 Example 2 137.9-146.8 0.31371 101.96 Comparative Example 1 97.2-122.1 0.7597 103.09 Comparative Example 2 98.7-121.3 0.6532 102.87 Comparative Example 3 96.1-120.6 0.7463 103.72

[0075] It can be seen from Table 2 that, relative to the comparative example, the crystal form prepared by the method of the present invention has a higher melting point, and lower water content and hygroscopicity.

[0076] Table 3

[0077]

[0078] It can be seen from Table 3 that the crystal form with a specific crystal form prepared by the method of the present invention has a small change in purity as the storage time increases, indicating that the crystal form prepared by the method of the present invention is not easy to deteriorate and is easy to preserve. Compared with the amorphous nucleoside prepared in the comparative example, the nucleoside with a specific crystal form of the present invention is beneficial to improving the purity of the phosphoramidite monomer product.

[0079] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A crystalline form of a compound represented by formula (1), characterized in that: The characteristic peaks 2θ of the X-ray powder diffraction pattern of the crystal form include 10.00°±0.2°, 12.08°±0.2°, 14.76°±0.2°, 16.90°±0.2°, 18.90°±0.2°, 19.30°±0.2°, 20.16°±0.2°, 21.38°±0.2°, 23.96°±0.2°, and 24.36°±0.2°; 2. The crystal form according to claim 1, wherein The characteristic peak 2θ of the X-ray powder diffraction pattern of the crystal form also includes 8.98°±0.2°, 13.6°±0.2°, 17.8°±0.2°, 22.80°±0.2°, 25.22°±0.2°, 27.30°±0.2°, 28.20°±0.2°, 29.26°±0.2°, 30.10°±0.2°, 30.72°±0.2°, 31.30°±0.2°, 32.40°±0.2°, 34.26°±0.2°, 35.92°±0.2°, 36.90°±0.2°, and 38.76°±0.2°; And / or, the structure of the compound represented by formula (1) is 3. The crystal form according to claim 1, wherein The X-ray powder diffraction pattern of the crystal form is shown in FIG1 .

4. The crystal form according to claim 1, wherein The melting point of the crystalline form is 137-148°C.

5. A method for preparing the crystal form according to any one of claims 1 to 4, characterized in that: The method comprises: mixing the compound represented by formula (1) with acetonitrile, heating to dissolve the compound represented by formula (1), and then cooling to crystallize to obtain the crystal form of the compound represented by formula (1).

6. The method according to claim 5, wherein: The amount of acetonitrile used is 6-12 mL per gram of the compound represented by formula (1); And / or, the heating temperature is 65-85°C; And / or, the crystallization temperature is 5-25°C. Preferably, the crystallization is carried out under stirring.

7. The method according to claim 5, wherein: The preparation method of the compound represented by formula (1) comprises: mixing the compound represented by formula (II) with dimethoxytriphenylmethane in the presence of a base and a solvent, and then reacting to obtain the compound represented by formula (1); Preferably, the compound represented by formula (II) is 8. The method according to claim 7, wherein: The solvent is at least one of pyridine, dichloromethane and dimethylformamide; and / or, the base comprises at least one of pyridine, triethylamine and N,N-diisopropylethylamine; and / or, for each millimole of the compound represented by formula (II), the amount of the base used is 1-20 mmol, the amount of the solvent used is 3-8 mL, and the amount of dimethoxytriphenylmethane used is 1-2 mmol; And / or, the compound represented by formula (II) is mixed with dimethoxytriphenylmethane by dropping a dichloromethane solution containing dimethoxytriphenylmethane into the compound represented by formula (II).

9. The method according to claim 7, wherein: The reaction conditions include: temperature of 15-20°C and time of 10-16h; And / or, the preparation method of the compound represented by formula (1) further comprises: after the reaction is completed, adding a quenching agent to the reaction system for quenching, then extracting with dichloromethane to obtain an organic phase containing the compound represented by formula (II), then washing the organic phase with saturated lemon water solution, saturated sodium chloride, and saturated sodium bicarbonate, respectively, and then drying.

10. Use of the crystalline form of the compound represented by formula (1) according to any one of claims 1 to 4 in improving the purity of phosphoramidite monomers; preferably, the use comprises using the compound represented by formula (1) having the crystalline form described in any one of claims 1 to 4 as a raw material for synthesizing phosphoramidite monomers.